On equation x^q=a over Q_p - Mukhamedov, Farrukh; Saburov, Mansoor (Academic Press Inc., 2013)
In this paper we provide a solvability criterion for the monomial equation x^q = a over Qp for any natural number q. As an application of the result, we describe a relationship between q and p in which the number −1 is the q-th power of some p-adic number.